2016
DOI: 10.4103/2230-8210.190527
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic function and vascular profile in subclinical hypothyroidism: Increased beat-to-beat QT variability

Abstract: Background:Patients with subclinical hypothyroidism (SH) may have higher incidence of coronary heart disease and autonomic dysfunction.Design of the Study:Prospective case control study.Aim and Objectives:To evaluate beat-to-beat QT variability and vascular stiffness in patients with SH compared to normal controls.Materials and Methods:We compared linear and nonlinear measures of cardiac repolarization liability using beat-to-beat QT intervals derived from the surface electrocardiogram during supine posture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“… Author Year Country Participants (SCH/EU) Age (SCH/EU) Study design TSH cutoff value T4 measured? Measure outcomes NOS Score Ali Aydogdu 33 2017 Turkey 30/30 37.70 ± 13.54/40.96 ± 13.39 Case-control study ≥5.5 mIU/L + EAT thickness 7 Pramila Kalra 39 2016 Canada 58/49 31.83 ± 8.91/32.42 ± 9.98 Case-control study >4.5 mIU/L + PWV 5 Edip Unal 50 2017 Turkey 38/38 8.1 ± 3.6/8.9 ± 2.4 Case-control study >4.2 mIU/L + CIMT 8 Irmak Sayin 48 2016 Turkey 44/42 41.2 ± 15.9/42.1 ± 13.5 Case-control study >5.0 mIU/L + EAT thickness 8 Mustafa Altay 30 2017 Turkey 35/30 34.4 ± 10.3/32.5 ± 7.5 Case-control study + CIMT 4 Yasemin Isik-Balci 38 2016 Turkey 53/31 9.25 ± 4.29/7.19 ± 5.15 Case-control study + CIMT 4 Dilek Arpaci 31 2016 Turkey 41/35 34.07 ± 6.70/31.82 ± 5.57 Case-control study >5.4 mIU/L + EA...…”
Section: Methodsmentioning
confidence: 99%
“… Author Year Country Participants (SCH/EU) Age (SCH/EU) Study design TSH cutoff value T4 measured? Measure outcomes NOS Score Ali Aydogdu 33 2017 Turkey 30/30 37.70 ± 13.54/40.96 ± 13.39 Case-control study ≥5.5 mIU/L + EAT thickness 7 Pramila Kalra 39 2016 Canada 58/49 31.83 ± 8.91/32.42 ± 9.98 Case-control study >4.5 mIU/L + PWV 5 Edip Unal 50 2017 Turkey 38/38 8.1 ± 3.6/8.9 ± 2.4 Case-control study >4.2 mIU/L + CIMT 8 Irmak Sayin 48 2016 Turkey 44/42 41.2 ± 15.9/42.1 ± 13.5 Case-control study >5.0 mIU/L + EAT thickness 8 Mustafa Altay 30 2017 Turkey 35/30 34.4 ± 10.3/32.5 ± 7.5 Case-control study + CIMT 4 Yasemin Isik-Balci 38 2016 Turkey 53/31 9.25 ± 4.29/7.19 ± 5.15 Case-control study + CIMT 4 Dilek Arpaci 31 2016 Turkey 41/35 34.07 ± 6.70/31.82 ± 5.57 Case-control study >5.4 mIU/L + EA...…”
Section: Methodsmentioning
confidence: 99%
“…Cacciatori et al suggested that thyroid hormone deficiency was associated with an increased sympathetic influence on the autonomic cardiovascular system. Some studies demonstrated that SH increased the cardiovascular risk factors, including altered lipid profile, impaired cardiac contractility, decreased cardiac output, increased systemic vascular resistance and cardiac electrical abnormalities (16)(17)(18). Galetta et al showed that the patients with SH had a higher QTd and lower heart rate variability (HRV) measurements compared with the healthy control group, and that the QTd was positively associated with TSH value, with the measurements returning to normal after treatment (9).…”
Section: Discussionmentioning
confidence: 99%
“…O hipotireoidismo subclínico (HS), uma das disfunções tireoidianas existentes, é bioquimicamente definido pela concentração elevada do hormônio estimulador da tireoide associado a uma concentração normal de tiroxina livre, de acordo com o valor de referência populacional específico (KALRA et al, 2016).…”
Section: Fundamentação Teóricaunclassified